Design of an Antifungal Surface Embedding Liposomal Amphotericin B Through a Mussel Adhesive-Inspired Coating Strategy - Alves, Diana; Vaz, Ana Teresa; Grainha, Tânia; Rodrigues, Célia F.; Pereira, Maria Olívia (Frontiers in Chemistry, 2019)
Microbial colonisation of urinary catheters remains a serious problem for medicine as it often leads to biofilm formation and infection. Among the approaches reported to deal with this problem, surfaces functionalization to render them with antimicrobial characteristics, comprises the most promising one. Most of these strategies, however, are designed to target bacterial biofilms, while fungal biofilms are much less taken into account. In real-life settings, fungi will be inevitably found in consortium with bacteria, especially in the field of biomaterials. The development of antifungal coating strategies to be combined with antibacterial approaches will be pivotal for the fight of biomaterial-associated infections. The main goal of the present study was, therefore, to engineer an effective strategy for the immobilization of liposomal amphotericin B (LAmB) on polydimethylsiloxane (PDMS) surfaces to prevent Candida albicans colonization. Immobilization was performed using a two-step mussel-inspired coating strategy, in which PDMS are first immersed in dopamine solution. Its self-polymerization leads to the deposition of a thin adherent film, called polydopamine (pDA), which allowed the incorporation of LAmB, afterwards. Different concentrations of LAmB were screened in order to obtain a contact-killing surface with no release of LAmB. Surface characterization confirmed the polymerization of dopamine and further functionalization with LAmB yielded surfaces with less roughness and more hydrophilic features. The proposed coating strategy rendered the surfaces of PDMS with the ability to prevent the attachment of Candida albicans and kill the adherent cells, without toxicity towards mammalian cells. Overall results showed that LAmB immobilization on a surface retained its antifungal activity and reduced toxicity, holding therefore a great potential to be applied for the design of urinary catheters. Since the sessile communities commonly found associated to these devices exhibit a polymicrobial nature, the next challenge will be to co-immobilize LAmB with antibacterial agents to prevent the establishment of catheter urinary-associated infections.